Venäläisten sotilasyritysten rooli Saharan eteläpuolisessa Afrikassa 2000-luvulla - Kilpiö, Taneli (2024)
This master’s thesis addresses the role of Russian private military companies (PMC) in Sub-Saharan Africa in the 21st century. The purpose of the thesis is to increase understanding of Russian PMC’s, such as the Wagner Group, which have received significant media attention but remain partly poorly understood. In Finland, there is little research data available on Russian PMC activities, especially regarding the Sub-Saharan Africa. The thesis maps out the role of Russian PMC’s in the security sector and compares how their role differs from, for example, Western and African PMC’s. The role of the PMC refers to commonly known practices of Western PMC’s, such as site protection, protection of key personnel, training services, and, as a less common role, direct use of military force in combat tasks. The method used in the thesis is a systematic literature review, and the analysis is based on scientific sources. The thesis presents a framework of the key roles of PMC’s, which is constructed from literature of background research, and then compares how specifically Russian PMC’s fit into this framework. The thesis analyses, whether there are differences between Russian and Western PMC’s, if there are similarities or, whether totally new roles emerge outside of the framework. The conclusion is that the role of Russian PMC’s in the region differs significantly from Western and African counterparts. Russian PMC’s are not driven by business interests, but are rather an extension of Russia's military organization. Their key roles in Sub-Saharan Africa include site protection, protection of key personnel, training and advisory services, counter-insurgency operations, and as a distinguishing factor, information warfare and election interference. In all cases, the clients of the Russian PMC’s have been the local state administrations. The purpose of the PMC’s is to support Russia's strategic objectives in Africa, which include supporting the continuity of pro-Russian governments, arms trade, protection of critical infrastructure, acquisition of rare earth metals, and spreading a positive image of Russia. Russia has a fertile ground in Africa and more freedom of action to echo its own agenda, as African states do not form a cohesive group ready to fully support Western actions and ideologies. For this purpose, Russian PMC’s serve as a flexible tool supporting Russia's objectives in Africa.